2001
DOI: 10.1086/321993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Entomopathogenic Nematodes for the Biological Control of Crop Pests: A Nonequilibrium Approach

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The University of Chicago Press andThe American Society of Naturalists are collaborating with JSTOR to digitize, preserve and extend access to The American Naturalist.http://ww… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Typically, the different trials, working with different nematode strains and different fly species in different growing conditions, all lead to different recommended doses. Previous theoretical work (Fenton et al . 2000, 2001) has shown that control success can be very sensitive to certain biological parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the different trials, working with different nematode strains and different fly species in different growing conditions, all lead to different recommended doses. Previous theoretical work (Fenton et al . 2000, 2001) has shown that control success can be very sensitive to certain biological parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these models enable us to include one essential feature of the sciarid fly–nematode interaction: only the larval stages of the sciarid fly are susceptible to infection. We have previously developed such a stage‐structured model, based on our earlier SI model, and used it to explore a number of specific short‐term control scenarios in a range of crop pest systems (Fenton et al . 2001).…”
Section: Methodsmentioning
confidence: 99%
“…EPNs are often applied as short-term inundative biological control agents in large numbers to bring about a rapid and severe decline in pest numbers [17,23,48], but only a fraction of these successes was found in a host [17]. In addition, the susceptibility of target insects varies depending on nematode species and strains [17,30].…”
Section: Discussionmentioning
confidence: 99%
“…The infection efficiency of EPNs relies on the enhanced pathogenicity of their bacterial symbiont [31,33]. Initially, the nematode enters into the insect's body via natural openings, with a posterior release of the symbiotic bacteria into the host hemocoel, causing septic shock and killing the insect in 24-48 h [26,[38][39][40]. This enables the optimal conditions for EPNs' reproduction and multiplication before the insect's death.…”
Section: Introductionmentioning
confidence: 99%